The French Revolution: The Origins of a Modern Liberal Political Culture? - Leith, James (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1991)
AbstractRecently it has been argued that the chief legacy of the French Revolution was that it provided a prototype of a modern liberal political culture. This paper argues that, while some of the features of such a political culture did appear during the revolutionary decade, the revolutionaries never discarded an ancient conception of sovereignty which insisted that political will had to be unitary and indivisible. This led to rejection of political parties, legitimate opposition, and pluralism. The debates in the Constituent Assembly already reveal these illiberal tendencies. The Declaration of the Rights of Man, with its apparent emphasis on individual rights, might seem to have counterbalanced these tendencies, but two clauses inserted at the insistence of Abbé Sieyès vested sovereignty in the nation and asserted that law must be the expression of the general will. These clauses transformed the rights of the individual into the rights of the Leviathan. The insistence on a unified will was revealed in the allegorical figures, symbols, and architectural projects of the period. The figure of the demigod Hercules, which came to represent the People, conveyed a monolithic conception of the citizenry in complete contradiction to the conception of them in a pluralistic liberal democracy. Also the fasces, the tightly bound bundle of rods with no power to move independently, suggested a conception of the body politic at odds with that of a variegated liberal society. If such unity did not exist, it was to be created by the rituals performed in Temples décadaires every tenth day, the republican Sunday. Those who would not join this vast congregation would be excised or coerced. Moreover, throughout the decade there were various theories of revolutionary government at odds with liberal ideals: the unlimited power of a constituent body, the concentration of power in a tribune or dictator, or the dictatorship of a committee. Such notions, too, were important for the future.